Relational database design with microcomputer applications - Jackson, Glenn A. (Englewood Cliffs, N.J. : Prentice Hall, 1988)
As the titles indicates, the book is an introduction to relational database design. The main emphasis of the book is the investigation of the problem of designing the database to be used with a standard database management system, like dBASE III. The goal is to outline a database design process that can be understood by an average microcomputer user.
Includes index.
Includes bibliographical references: p. 201.
II 15/01/2019
Loans
Keywords: Relational databases; Microcomputers; Database design